Telepsychiatry in the emergency department: a pilot study on remote psychiatric assessment in the Netherlands - Jorn Eerhard; Heleen van ’t Oever; Cherryl V.S. van Alst; Rosa L.A. de Vries; Dieuwke Douma-den Hamer; Sander Manders; Carine J.M. Doggen; Gert-Jan Mauritz (International Journal of Emergency Medicine)
Abstract Background Emergency Departments (EDs) increasingly manage patients in acute psychiatric crisis, often facing delays due to limited on-site psychiatric specialists. Telepsychiatry offers a potential solution, but its feasibility and acceptance in Dutch EDs remain underexplored. This pilot study aimed to assess the feasibility, technical aspects, and acceptance of telepsychiatry consultations in a Dutch ED setting. Methods This two-phase observational pilot study was conducted at a large hospital ED in the Netherlands. During a three-month baseline-phase (Aug–Oct 2024), eligible adult patients received standard in-person psychiatric consultations. In the subsequent three-month pilot-phase (Nov 2024–Jan 2025), patients were evaluated via secure video consultation with a remote psychiatrist. To assess feasibility and technical execution, lead times, including consult request and consult start time, time until disposition decision and ED length of stay, were recorded. To further evaluate technical execution and acceptance, patients and ED staff were asked to complete satisfaction questionnaires, after each telepsychiatry consult. Results Eleven patients were included during the baseline-phase and 17 during the pilot-phase. All telepsychiatry consultations were completed successfully, with only minor technical issues. Patient satisfaction was high, and psychiatrists and ED staff rated the consultations as effective and efficient. Furthermore, mean time from consult request to disposition decision was about an hour less during the telepsychiatry phase (approximately 45 vs. 106 min in the baseline phase). Conclusion Telepsychiatry in the ED appears feasible, technically reliable, and well accepted by both patients and ED staff. This pilot study supports further exploration of telepsychiatry as a tool to enhance emergency psychiatric care delivery in the Netherlands.